Intensive perioperative glucose control does not improve outcomes of patients submitted to open-heart surgery: a randomized controlled trial (Clinics, 2009)
BACKGROUND: The objective of this study was to investigate the relationship between different target levels of glucose and the clinical outcomes of patients undergoing cardiac surgery with cardiopulmonary bypass. METHODS: We designed a prospective study in a university hospital where 109 consecutive patients were enrolled during a six-month period. All patients were scheduled for open-heart surgery requiring cardiopulmonary bypass. Patients were randomly allocated into two groups. One group consisted of 55 patients and had a target glucose level of 80-130 mg/dl, while the other contained 54 patients and had a target glucose level of 160-200 mg/dl. These parameters were controlled during surgery and for 36 hours after surgery in the intensive care unit. Primary outcomes were clinical outcomes, including time of mechanical ventilation, length of stay in the intensive care unit, infection, hypoglycemia, renal or neurological dysfunction, blood transfusion and length of stay in the hospital. The secondary outcome was a combined end-point (mortality at 30 days, infection or length of stay in the intensive care unit of more than 3 days). A p-value of